Da fragilidade à consistência: a RBC entra em uma Nova Era - Dias Filho, Claudemir Rodrigues; Bruni , Aline; Telles, Bruno; Gomes , Juliano de Andrade (Revista Brasileira de Criminalística, 2022)
Editorial